Iraq : 2019 Article IV Consultation and Proposal for Post-Program Monitoring-Press Release; Staff Report; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation and Proposal for Post-Program Monitoring highlights that Iraq's social conditions remain harsh following the war with ISIS, with slow progress at reconstruction, weak public services and a lack of job opportunities. In the absence of policy changes, a widening budget deficit is expected to divert resources away from essential investment to rebuild the country and improve public services, while eroding reserves and posing risks to medium-term sustainability. Expenditure rigidities and limited fiscal buffers imply a significant vulnerability to oil price shocks in a context of volatile prices. The fiscal and external positions are expected to continue to deteriorate over the medium term absent policy changes-with reserves falling below adequate levels and fiscal buffers eroded. In a context of highly volatile oil prices, the major risk to the outlook is a fall in oil prices which would lower exports and budgetary revenues, leading to an even sharper decline in reserves or higher public debt. Geopolitical tensions, the potential for social unrest in a context of weak public services and lack of progress in combatting corruption pose further risks.